Comparação de comunidades de Coleoptera em cultivo de eucalipto e fragmento de Floresta Estacional Semidecidual na região de Sorocaba, São Paulo - Dias, Luiz Philippe (Universidade Federal de São Carlos, 2018)
Studies on ecosystems with different levels of change are important to assess the impact these changes have on biodiversity. Coleoptera are used as environmental bioindicators because of the diversity and variety of their food habits. The objective of this work was to compare the community of Coleoptera in native and cultivated area. The beetles were collected with light traps every two weeks from September 2016 to August 2017 in Eucalyptus platyphylla F. Muell (Myrtaceae) and a semideciduous seasonal forest fragment (FES) in the region of Sorocaba, São Paulo. A total of 1116 individuals, 657 in E. platyphylla and 459 in FES were captured. Coleoptera abundance was similar in both environments, with most of the families observed in both areas. There was no predominance of individuals of a particular trophic group in the environments, so that both herbivorous and predator families had high abundance in the studied areas. Most coleoptera in E. platyphylla and FES fragment occurred in the hot period between October 2016 and March 2017, with population peaks in October. Curculionidae, Elateridae and Carabidae showed a positive correlation with temperature.
Comparation of communities of Coleoptera in eucalyptus cultivation and fragment of Semideciduous Seasonal Forest in the region of Sorocaba, São Paulo
Keywords: Praga florestal; Inimigos naturais; Armadilha luminosa; Flutuação de abundância; Forest pest; Natural enemies; Luminous trap; Abundance fluctuation; Coleóptero; Ecossistemas; Biotic communities; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA::PROTECAO FLORESTAL